Cardiac K2P13.1 (THIK-1) two-pore-domain K+ channels: pharmacological regulation and remodeling in atrial fibrillation - Staudacher, Ingo; Seehausen, Sebastian; Illg, Claudius; Lugenbiel, Patrick; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (Progress in biophysics & molecular biology, 2018)
Cardiac two-pore-domain potassium (K2P) channels have been proposed as novel antiarrhythmic targets. K2P13.1 (THIK-1) channels are expressed in the human heart, and atrial K2P13.1 levels are reduced in patients with atrial fibrillation (AF) or heart failure. The first objective of this study was to investigate acute effects of antiarrhythmic drugs on human K2P13.1 currents. Second, we assessed atrial K2P13.1 remodeling in AF pigs to validate the porcine model for future translational evaluation of K2P13.1-based antiarrhythmic concepts. K2P13.1 protein expression was studied in domestic pigs during AF induced by atrial burst pacing. AF was associated with 66% reduction of K2P13.1 levels in the right atrium at 21-day follow-up. Voltage clamp electrophysiology was employed to elucidate human K2P13.1 channel pharmacology in Xenopus oocytes. Propafenone (−26%; 100μM), mexiletine (−75%; 1.5mM), propranolol (−38%; 200μM), and lidocaine (−59%; 100μM) significantly inhibited K2P13.1 currents. By contrast, K2P13.1 channels were not markedly affected by quinidine, carvedilol, metoprolol, amiodarone and verapamil. Concentration-dependent K2P13.1 blockade by mexiletine occurred rapidly with membrane depolarization and was frequency-independent. Mexiletine reduced K2P13.1 open rectification properties and shifted current-voltage relationships towards more negative potentials. In conclusion, atrial expression and AF-associated downregulation of K2P13.1 channels in a porcine model resemble human findings and support a general role for K2P13.1 in AF pathophysiology. K2P13.1 current sensitivity to antiarrhythmic drugs provides a starting point for further development of an emerging antiarrhythmic paradigm.
Gesehen am 06.08.2019
Im Titel ist "2P" in K2P13.1 tiefgestellt
Im Titel ist "+" in K+ hochgestellt